The impact of monitor choice on insurer loss reserves. Issue 1 (8th February 2023) - Bisco, Jill; McCullough, Kathleen; Montesinos Yufa, Hugo Moises; Tice Sirmans, Eleanor
Abstract: This paper examines the association between monitoring and earnings management by property‐casualty insurers. Prior literature has evaluated the impact of auditors and actuaries on insurer reserving. We extend this work by considering the nonrandom nature of monitor assignment. We model the insurer decisions regarding choice of auditor and actuary jointly using a Heckman selection model. Consistent with prior literature, we account for potential loss reserving incentives that may confound these decisions. We find that the use of internal actuaries is significantly related to higher reserve errors, but this is reduced, but not fully offset, when the internal actuary is an officer of the insurer. We find lower reserve error for auditors from a Big N firm. However, the use of an auditor and actuary from the same Big N firm is significantly related to higher reserve errors.